Wood in Civil Engineering - Concu, Giovanna (IntechOpen, 2017)
Wood is a natural building material: if used in building elements, it can play structural, functional and aesthetic roles at the same time. The use of wood in buildings, which goes back to the oldest of times, is now experiencing a period of strong expansion in virtue of the sustainable dimension of wood buildings from the environmental, economic and social standpoints. However, its use as an engineering material calls for constant development of theoretical and experimental research to respond properly to the issues involved in this. In the single chapters written by experts in different fields, the book aims to contribute to knowledge in the application of wood in the building industry.